Viscosity of yttrium oxide (Y2O3) and magnesium-aluminum spinel (MgAl2O4) nanopowder suspensions in ethyl alcohol (Archives of Mechanics - Test, 2013)
We report results of rheological experiments on suspensions of nanopowders. In this work we have used two ceramic nanopowders such as magnesium-aluminum spinel (S30CR Baikowski – MgAl2O4) and yttrium oxide (Y2O3) suspended in ethyl alcohol. Rheological studies have been carried out using several experimental systems including Haake Mars 2 rheometer (Thermo Electron Corporation, Karlsruhe, Germany) and Rheo-NMR (Bruker BioSpin, Rheinstetten, Germany). Measurements of dynamic viscosity in the range of shear rates from 0,01 s-1 to 2000 s-1 and the temperature range from -15°C to 20°C has been conducted. Most of the samples exhibited a non-Newtonian nature.